Expression of a bacterial gene in plants mediated by infectious geminivirus DNA - Ward, A. (1988)
A viable coat protein deletion mutant of cassava latent virus (CLV) DNA 1 has been isolated, suggesting that this geminivirus might be exploited as a gene replacement vector. An extensive deletion of 727 nucleotides within the coat protein gene renders DNA 1 non-infectious. Chimeric clones have been constructed in which the deleted coat protein open reading frame has been replaced by the coding region of the bacterial chloramphenicol acetyl transferase (CAT) gene. Infectivity is restored to DNA 1 when the CAT gene is inserted in either orientation, producing symptoms typical of CLV infection. The results demonstrate that the coat protein plays no essential role in virus spread throughout the host. Levels of CAT expression of 80 U/mg soluble protein occur in systemically infected Nicotiana benthamiana leaves when the CAT gene is fused in-frame to the amino terminus of the coat protein, providing a sensitive assay for viral DNA replication.